A novel heterogeneous-particle model based on peridynamics for flexural mechanical properties of randomly oriented fiber reinforced composites. (15th August 2022) - Qu, Peng; Wan, Yi; Fang, Guangqiang; Guo, Anfu; Liu, Gang; Takahashi, Jun
Abstract: On the basis of peridynamic (PD) theory, a heterogeneous-particle model is proposed to investigate the flexural mechanical properties of a chopped carbon fiber tape reinforced thermoplastic (CTT). In contrast to the numerical analysis on the tensile behavior, the simulation of flexural behavior of CTT is challenging because a full-scale model rather than a representative volume element (RVE) is required in the modeling. The novelty is that the mesoscopic structure, such as the random orientation of fibers and the thickness of tapes, are represented in the simulation of flexural mechanical behavior. This model successfully simulates the flexural fracture morphologies, well predicts the flexural mechanical properties, and effectively captures the characteristic of the scatter in flexural properties. The effects of tape thickness, fiber orientation, support span and specimen thickness on the flexural behavior of CTT are investigated by this model. The influencing mechanism of these factors is revealed through this model.